Pengaruh Variasi Jenis Daun Talas Pada Besarnya Beda Potensial Yang Dihasilkan Pada Proses "Harvesting Energy" - Firdaus Fitraryansyah (Jurnal Teknik Mesin, 2021)
Harvesting energy is energy harvesting that is environmentally friendly by using natural resources to produce renewable energy in the form of electrical energy. Harvesting energy that is commonly used is solar cells during the dry season which are considered more efficient and have many advantages, it does not cause air pollution or noise pollution, but during the rainy season solar cells cannot receive enough solar energy to be stored so they cannot produce electrical energy. The harvesting energy that will be used at this research is by dripping aquades droplets on the surface of the taro leaves with a drop distance of 5 cm and a tilt angle of 20° and varying the types of taro leaves used. On the underside of the leaf will be coated using aluminum foil as an electrode. The results of the research showed that the taro leaves of the Bogor taro species were colocasia esculenta (L) schott. generates an electrical voltage of 0.3964 volts and is the highest point of the electrical voltage produced. As the results, Taro Bogor colocasia gigantae (Bl.) Hook.f the electrical voltage generated is 0.2929 volts and the resulting electric voltage of taro is 0.3666 volts. The surface of the taro leaves contains elements of Mg, K, Ca which will bind to each other when they meet with H20, this reaction causes an electron jump.